ANALISIS OPTIMASI DAN RISIKO USAHA PADA USAHATANI CABAI MERAH DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Damayanti, Yusma; Nurchaini, Dewi Sri; Ulma, Riri Oktari (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Red chili farming is relatively risky, but farming has promising profit opportunities. Kumpeh subdistrict can potentially provide business red chili commodities with the most significant harvest and production area. The availability and condition of the land support for red chili farming. This study aims to optimize production factors in red chili farming and analyze business risks farmers face in growing red chili peppers. This research was conducted in Kumpeh District of Muaro Jambi Regency with sample areas, namely Mekar Sari Village and Maju Jaya Village. The number of samples in this study was 118 farmers. The determination of sample farmers is done using random sampling techniques. Optimization analysis of red pepper farming factors was conducted using the Cobb-Douglas production function with economic efficiency criteria on production factors. Meanwhile, the amount of business risk is calculated from the measure of the coefficient of variation and the lower-income limit. The results showed that farmers in the research area's use of land production, fertilizers (NPK, KCL, SP36, manure), and pesticides (liquid and solid) in red chili farming had not achieved economic efficiency. Economically, a farmer's optimum production is greater than the amount he uses. Similarly, the use of labor production factors that are not economically efficient. Meanwhile, the coefficient of variation in red chili income is worth more than 0.5. This condition causes the lower limit of income that may be received to be negative. Red chili farming in the research area is not safe from possible losses. Still, red chili farming is quite profitable in terms of farming feasibility, with an R/C ratio greater than 1.